PERAN MATERI PENDIDIKAN AGAMA ISLAM DI SEKOLAH DALAM MEMBENTUK KARAKTER KEBANGSAAN DI ERA DIGITAL - Abdul Fadhil; Muh Fauzan Nastiar, Juanita Nur Istiqomah Putri, Arga Sabda Wiguna, Ahmad Ridwan (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research explores the role of Islamic Religious Education (PAI) materials in schools in shaping national character in the digital era. Good character, based on Islamic values such as honesty, sincerity, and responsibility, is an important element in building the identity of a Muslim who loves the homeland. PAI aims to instill moral and spiritual values amid the challenges of a secular national education system, where the focus is often more on knowledge transfer than character building. Through a theoretical study approach with a descriptive qualitative method, this study analyzes various literature to understand the extent to which PAI can strengthen students' national values and morality. The results show that the comprehensive and consistent implementation of PAI in the educational curriculum can contribute significantly in overcoming the morality crisis among students, equipping them with characters that support the welfare of the community and the nation